Analisis Yuridis Pengembalian Barang Bukti Dalam Tindak Pidana Perikanan (Juridical Analysis Of Returns Of Investigation Goods Action Of Fisheries Criminal) - Ibrahim Nainggolan (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Fisheries in Indonesia is one of the natural resources which is a gift from God the Almighty that must be managed in such a way that can improve people's welfare in accordance with the provisions of the 1945 Constitution Article 33 paragraph (3) stated, "Earth and water and the natural wealth contained therein is controlled by the State and used for the greatest prosperity of the people. This writing uses normative juridical legal research methods (normative research) with descriptive analytical research specifications that use secondary data. The procedure for collecting data is in the form of documentation of notes or quotations, search of legal literature, books and others related to the identification of problems both offline and online which are then analyzed through the content analysis method (content analysis method) with a focus on the problem of how the enforcement system criminal law in fisheries crime, how is the legal regulation regarding the return of evidence in a fishery crime. From the results of the study, it is known that the criminal law enforcement system in fisheries is included in the special provisions with special legislation arrangements.